The Correlation Between Click-Evoked Auditory Brainstem Responses and Future Behavioral Thresholds Determined Using Universal Newborn Hearing Screening. (12th October 2021) - Cheng, Ting-Yu; Tsai, Ching-Fang; Luan, Chih-Wei
This retrospective study was undertaken to assess the correlation between click-evoked auditory brainstem responses and behavioral hearing tests. We recruited a total of 16646 infants born in Ditmanson Medical Foundation Chia-Yi Christian Hospital, Taiwan, from 2012 to 2018 for such assessment purpose. Their data including the click-evoked auditory brainstem response (ABR), referral, and diagnostic follow-up were collected. Spearman correlation method was employed to assess the relationship between ABR and pure-tone threshold. The correlation between the click-evoked ABR that met the National Health Administration standards and the click-evoked ABR derived from estimates before and after the 2.5 years of age effectively predicted the toddlers' pure-tone audiometry (PTA) thresholds at 2–4 kHz.